Anti-Adipogenic Polyacetylene Glycosides from the Florets of Safflower (Carthamus tinctorius) - Baek, Su Cheol; Yi, Sang Ah; Lee, Bum Soo; Yu, Jae Sik; Kim, Jin-Chul; Pang, Changhyun; Jang, Tae Su; Lee, Jaecheol; Kim, Ki Hyun (MDPI, 2021)
Safflower (Carthamus tinctorius) is an annual herb belonging to the Compositae family; it has a history of use as a food colorant, dye, and medicine in oriental countries. LC-MS-UV-based chemical analysis of extract of the florets of C. tinctorius led to the isolation of two new C-10-polyacetylene glycosides, (8Z)-decaene-4,6-diyne-1,10-diol-1-O-beta-d-glucopyranoside (1) and (8S)-deca-4,6-diyne-1,8-diol-1-O-beta-d-glucopyranoside (2), together with five known analogs (3-7). The structures of the new compounds were determined by using 1D and 2D NMR spectroscopic data and HR-MS data, as well as chemical transformations. Of compounds 1-7, compounds 2, 3, and 4 inhibited the adipogenesis of 3T3-L1 preadipocytes, whereas compounds 1 and 6 promoted adipogenesis. Compounds 2, 3, and 4 also prevented lipid accumulation through the suppression of the expression of lipogenic genes and the increase of the expression of lipolytic genes. Moreover, compounds 3 and 4 activated AMPK, which is known to facilitate lipid metabolism. Our findings provide a mechanistic rationale for the use of safflower-derived polyacetylene glycosides as potential therapeutic agents against obesity.